Green Plastering Mortars Based on Clay and Wheat Straw. (2016) - Andres, Dana Maria; Manea, Daniela Lucia; Fechete, Radu; Jumate, Elena
Abstract: This paper is part of a larger project which seeks to promote traditional, organic materials with similar features to classic building materials used in construction, but with a lower price and a positive impact on human health. The aim of this study is to find a way to improve the mechanical characteristics of green plastering based on clay and wheat straw. Wheat straw is waste from agriculture, which most often are burnt in the fields, thus contributing to higher emissions of carbon dioxide. The study's objective is to achieve green mortars based on clay. To improve the mechanical characteristics, the influence of wheat straw as a reinforcing material was studied. It was studied how the geometric characteristics of wheat straw affect the properties of studied material.